Global DNA methylation and PTEN hypermethylation alterations in lung tissues from human silicosis - Zhang, Xianan; Jia, Xiaowei; Mei, Liangying; Zheng, Min; Yu, Chen; Ye, Meng (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Silicosis is a respiratory disease caused by long-term silica dust exposure. Our previous study has demonstrated that silica mediates the activation of phosphatidylinositol 3-kinase (PI3K)/phosphatase and tensin homolog deleted on chromosome 10 (PTEN)/serine or threonine kinase (AKT)/mitogen-activated protein kinases (MAPK)/AP-1 pathway in human embryo lung fibroblasts (HELFs). The purpose of this study is to identify genome-wide aberrant DNA methylation profiling in lung tissues from silicosis patients. Methods: We performed Illumina Human Methylation 450K Beadchip arrays to investigate the methylation alteration in formalin-fixed, paraffin-embedded (FFPE) lung specimens, immunohistochemistry to detect the level of c-Jun and PTEN proteins; methylation specific PCR (MS-PCR) to identify PTEN and c-Jun promoter methylation in HELFs. Results: We found 86,770 CpG sites and 79,660 CpG sites significantly differed in methylation status in early-stage and advanced-stage compared with GEO normal lung methylation data. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed the methylated status of MAPK signaling pathway was considered changed. The number of PTEN and c-Jun CpG promoter methylated-sites were increased in advanced-stage. Early-stage showed the positive expression of c-Jun and PTEN protein and negative or mild expression in advanced-stage. PTEN promoter was no differentially methylated and c-Jun promoter differed at 12 and 24 h in HELFs. Conclusions: Abnormal DNA methylation on genome-scale was implicated in silicosis, and PTEN promoter hypermethylation might be associated with decrease of PTEN protein.